2019
DOI: 10.1002/chem.201902529
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR Monitoring of Reversible Protein Post‐Translational Modifications: Class D β‐Lactamase Carbamylation and Inhibition

Abstract: Bacterial production of β‐lactamases with carbapenemase activity is a global health threat. The active sites of class D carbapenemases such as OXA‐48, which is of major clinical importance, uniquely contain a carbamylated lysine residue which is essential for catalysis. Although there is significant interest in characterizing this post‐translational modification, and it is a promising inhibition target, protein carbamylation is challenging to monitor in solution. We report the use of 19F NMR spectroscopy to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
(112 reference statements)
2
16
0
Order By: Relevance
“…The V128L and V128I variants of OXA-23 were produced and highly purified ( Fig. S4 ) ( 22 , 23 ). With nitrocefin, the k cat / K m values for OXA-23 V128I and V128L are lower than for WT OXA-23, because the K m values are substantially higher for both variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The V128L and V128I variants of OXA-23 were produced and highly purified ( Fig. S4 ) ( 22 , 23 ). With nitrocefin, the k cat / K m values for OXA-23 V128I and V128L are lower than for WT OXA-23, because the K m values are substantially higher for both variants.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the generality of these observations, the impact of substituting Val128 (equivalent to Val120 in OXA-48) on the activity of OXA-23, a clinically important class D SBL which shares 39% sequence identity with OXA-48, was also examined. The V128L and V128I variants of OXA-23 were produced and highly purified ( Figure S4) (22,23). With nitrocefin, the kcat/KM values for OXA-23 V128I and V128L are lower than for wild-type OXA-23, as the KM values are substantially higher for both variants.…”
Section: Steady State Kineticsmentioning
confidence: 99%
“…Class D enzymes require a lysine carbamate for catalysis, which is formed by reaction of an essential active site lysine with (bi)carbonate / carbon dioxide [28][29][30] (hence OXA assays were carried out with and without added bicarbonate). Notably, 3, like cyclic boronate 2 and VNRX-5133, was not highly potent against the Class D enzyme OXA-10, either with or without added bicarbonate (100 mM), and the pIC 50 value was reduced in the latter case (pIC 50 from 5.9 to 4.1; Table 1).…”
Section: Synthesis Of Thioether Substituted Cyclic Boronatementioning
confidence: 99%
“…The pIC 50 values of 3 against OXA-48 both in the absence and presence of bicarbonate were both substantially greater than for 2 and VNRX-5133(Table 1). 30 Recent work employing kinetic and biophysical (NMR and crystallography) analyses shows that different inhibitor classes interact with Class D OXA-enzymes in a manner that differently influences their lysine-carbamylation status. 28 The molecular basis of the difference in potency between 3 and 2 for OXA-10 and OXA-48 merits further investigation and will be the subject of future studies.…”
Section: Synthesis Of Thioether Substituted Cyclic Boronatementioning
confidence: 99%
“…Lysine decarboxylation of avibactam-acylated OXA-48 at neutral pH was also observed by King et al 15 Lohans et al 16 found that lysine carboxylation of OXA-48 was disfavored but not ablated by avibactam in solution using 13 C NMR. Using a novel 19 F NMR technique that did not require the presence of bicarbonate, van Groessen et al 17 later observed that avibactam derivatization of OXA-48 more substantially disfavored lysine carboxylation. Their suggested explanation for this effect was that a hydrogen bond from the nucleophilic serine, which is acylated by avibactam, stabilizes the carbamoyl lysine.…”
Section: Resultsmentioning
confidence: 99%